Relationship between community prevalence of obesity and associated behavioral factors and community rates of influenza‐related hospitalizations in the United States. Issue 5 (8th November 2012) - Charland, Katia M.; Buckeridge, David L.; Hoen, Anne G.; Berry, Jay G.; Elixhauser, Anne; Melton, Forrest; Brownstein, John S.
<x xml:space="preserve">Abstract</x> Please cite this paper as: Charland et al.(2012) Relationship between community prevalence of obesity and associated behavioral factors and community rates of influenza‐related hospitalizations in the United States. Influenza and Other Respiratory Viruses DOI: 10.1111/irv.12019. Background Findings from studies examining the association between obesity and acute respiratory infection are inconsistent. Few studies have assessed the relationship between obesity‐related behavioral factors, such as diet and exercise, and risk of acute respiratory infection. Objective To determine whether community prevalence of obesity, low fruit/vegetable consumption, and physical inactivity are associated with influenza‐related hospitalization rates. Methods Using data from 274 US counties, from 2002 to 2008, we regressed county influenza‐related hospitalization rates on county prevalence of obesity (BMI ≥ 30), low fruit/vegetable consumption (<5 servings/day), and physical inactivity (<30 minutes/month recreational exercise), while adjusting for community‐level confounders such as insurance coverage and the number of primary care physicians per 100 000 population. Results A 5% increase in obesity prevalence was associated with a 12% increase in influenza‐related hospitalization rates [adjusted rate ratio (ARR) 1·12, 95% confidence interval (CI) 1·07, 1·17]. Similarly, a 5% increase in the prevalence of low fruit/vegetable consumption and physical inactivity was associated with an increase of 12% (ARR 1·12, 95% CI 1·08, 1·17) and 11% (ARR 1·11, 95% CI 1·07, 1·16), respectively. When all three variables were included in the same model, a 5% increase in prevalence of obesity, low fruit/vegetable consumption, and physical inactivity was associated with 6%, 8%, and 7% increases in influenza‐related hospitalization rates, respectively. Conclusions Communities with a greater prevalence of obesity were more likely to have high influenza‐related hospitalization rates. Similarly, less physically active populations, with lower fruit/vegetable consumption, tended to have higher influenza‐related hospitalization rates, even after accounting for obesity.